Silver paste and preparation method and application thereof
The graphite emulsion coats silver powder to form a carbon-clad silver composite material, which solves the problem of silver migration in conductive silver paste, improves the electrical performance and adhesion of solar cells, and reduces costs.
Patent Information
- Application Number
- CN202411783398.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-05
AI Technical Summary
The existing conductive silver paste has silver migration problems in solar cells, resulting in reduced electrical performance and weakened adhesion, and is costly.
The silver is coated with graphite milk to form a composite material that coats silver with carbon. By mixing silver powder and graphite milk, the composite material is formed after drying, and combining glass powder and organic carrier to prepare a high-performance silver paste.
Effectively prevent the migration of silver ions, extend the service life of solar cells, improve electrical performance, adhesion and aging performance, while reducing costs.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the fields of solar energy, and in particular to a silver paste and a preparation method and application thereof. Background Art
[0002] Conductive silver paste for solar cells is a crucial raw material in the manufacture of solar photovoltaic cells. Its characteristics and applications are directly related to the conductivity, energy conversion efficiency and reliability of solar cells. Conductive silver paste is mainly composed of conductive phase silver powder, inorganic binder glass material, organic carrier and trace additives to improve battery performance. Conductive silver paste is used on both the front and back of solar photovoltaic cells. The front conductive silver paste is used to make the conductive path inside the battery. Especially in polycrystalline silicon cells, conductive silver paste is used to connect the metal grid between the cells to form the guidance and distribution of current. The back conductive silver paste is usually used as the back contact layer. This layer of conductive silver paste helps the current flow from the back of the battery to the back electrode, improving the conductivity efficiency of the battery.
[0003] Conductive silver paste is usually required to have a stable and good silver-silicon ohmic contact to ensure that the current flows smoothly between the silver electrode and the silicon substrate. High conductivity is also an important indicator to provide a low-resistance conductive path and improve the energy conversion efficiency of the battery. In addition, low cost is also required to reduce production costs and improve economy while ensuring performance. And good weldability, adhesion, and printing performance to ensure that the conductive silver paste performs well in printing and other processes. In the conductive silver paste, silver powder is the main component of the conductive silver paste. However, there is a problem of silver migration. The conductive efficiency is usually improved by increasing the amount of silver powder, but too much silver powder is easy to agglomerate, which makes the conductive efficiency reach a bottleneck and cannot be further improved. In addition, too much silver powder greatly increases the cost of the conductive silver paste.
[0004] Therefore, as a key component of electrode materials, it is of great significance to develop conductive silver paste with high performance and low cost. Summary of the invention
[0005] In view of the defects existing in the prior art, the purpose of the present invention is to provide a silver paste and a preparation method and application thereof. The silver paste of the present invention can improve the problem of silver migration and further improve the electrical performance of solar cells.
[0006] To achieve the above objectives, the first aspect of the present invention provides a silver paste comprising a composite material, glass powder and an organic carrier, wherein the raw materials of the composite material include silver powder and graphite emulsion.
[0007] Based on the above technical solution, the preparation method of the composite material comprises: mixing silver powder and graphite emulsion and drying. In the present invention, the structure of the carbon-coated silver composite material can be formed by the preparation method, thereby overcoming the problem of silver migration, thereby improving the conductivity and stability.
[0008] Based on the above technical solution, the formula of the graphite emulsion can be but is not limited to: in weight percentage, the graphite emulsion contains 9-11 weight% of graphite, 1-2 weight% of dispersant, 2-4 weight% of binder, 1-2 weight% of ammonia water, 0.8-1.8 weight% of thickener, and 81-85 weight% of water.
[0009] On the basis of the above technical solution, the dispersant is selected from one or more of sodium carboxymethyl cellulose, polyvinyl pyrrolidone, polyvinyl alcohol and gum arabic.
[0010] On the basis of the above technical solution, the binder is selected from silica sol.
[0011] On the basis of the above technical solution, the thickener is selected from carboxymethyl cellulose.
[0012] On the basis of the above technical solution, the weight ratio of silver powder to graphite emulsion is 1:0.2-0.5. For example but not limited to: the weight ratio of silver powder to graphite emulsion is 1:0.2-0.5, 1:0.3-0.5, 1:0.4-0.5, 1:0.2-0.4, 1:0.3-0.4, etc.
[0013] On the basis of the above technical solution, the particle size of the silver powder is 0.5-5μm. The particle size of the silver powder is, for example but not limited to, 0.5-5μm, 1-5μm, 1.5-5μm, 2-5μm, 2.5-5μm, 3-5μm, 3.5-5μm, 4-5μm, 4.5-5μm, 0.5-4μm, 1-4μm, 1.5-4μm, 2-4μm, 2.5-4μm, 3-4μm, 3.5-4μm, 0.5-3μm, 1-3μm, 1.5-3μm, 2-3μm, 2.5-3μm, etc.
[0014] On the basis of the above technical solution, the drying conditions include: temperature of 60-100°C and time of 2-10 hours. In the present invention, the drying temperature can be but not limited to 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, etc.
[0015] On the basis of the above technical solution, based on the total weight of the silver paste, the content of the composite material is 50-85 weight %, the content of the glass powder is 2-5 weight %, and the content of the organic vehicle is 14-45 weight %.
[0016] On the basis of the above technical solution, the glass powder is selected from one or more of borosilicate glass powder, alkali metal glass powder, ultra-white rolled glass powder and ultra-white float glass powder. In the present invention, for example but not limited to, based on the total weight of the glass powder, the content of SiO2 is 30-60 weight%, the content of PbO is 25-40 weight%, the content of Al2O3 is 0.1-3 weight%, the content of Na2O is 5-20 weight%, the content of K2O is 0.1-1 weight%, the content of MgO is 1-6 weight%, the content of CaO is 6-12 weight%, the content of MoO2 is 0-1 weight%, and the content of SnO2 is 0-1 weight%.
[0017] On the basis of the above technical solution, the organic carrier includes a solvent and optional additives.
[0018] On the basis of the above technical solution, the solvent is selected from one or more of diethylene glycol butyl ether acetate, dimethyl glutarate, dimethyl succinate and dimethyl adipate.
[0019] On the basis of the above technical solution, the additive is selected from one or more of a dispersant, a leveling agent, a thixotropic agent, a coupling agent and a defoaming agent. In the present invention, the dispersant, the leveling agent, the thixotropic agent, the coupling agent and the defoaming agent can be conventional options in the art, for example, the dispersant can be BYK-W980, etc.; the coupling agent can be a silane coupling agent, etc.; the leveling agent can be castor oil, etc.; the defoaming agent can be dimethyl silicone oil, etc. In the present invention, the additive can be added in an amount of 0-0.5% by weight based on the total weight of the silver paste. For example, but not limited to 0.1% by weight, 0.2% by weight, 0.3% by weight, 0.4% by weight, 0.5% by weight, etc.
[0020] On the basis of the above technical solution, the silver paste is a conductive silver paste for the front side of solar cells.
[0021] The second aspect of the present invention provides a method for preparing the above silver paste, comprising: mixing silver powder, composite material and organic carrier. The mixing may be, but is not limited to, rolling and dispersing evenly in a three-roll mill.
[0022] The third aspect of the present invention provides the use of the above-mentioned silver paste in solar cells.
[0023] Beneficial effects of the present invention:
[0024] The migration problem of silver is indeed an area worthy of attention, especially in applications such as solar cells, where silver is the main material of conductive silver paste and its impact is particularly significant. The migration problem may lead to a decrease in the electrical performance of solar cells and a weakening of adhesion. The present invention uses graphite emulsion to coat silver to form a composite material of a carbon-coated silver structure, and the carbon material is used as a protective layer and coated on the surface of the silver. The carbon material has excellent stability and barrier properties, and can effectively prevent the migration of silver ions, thereby extending the service life of solar cells and improving the electrical properties, adhesion and aging properties of solar cells prepared with silver paste. Moreover, the graphite emulsion of the present invention has low cost and can reduce the cost of silver paste. DETAILED DESCRIPTION
[0025] In the following technical description, for the sake of convenience of explanation, a plurality of details are provided to provide a full understanding of the disclosed embodiments. However, one or more embodiments can still be implemented without these details. In other cases, for the sake of embodiments, well-known structures and devices can be simplified for display.
[0026] The terms "first", "second", etc. in the description and claims of the disclosed embodiments and the above-mentioned embodiments are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the terms used in this way can be interchanged where appropriate, so that the embodiments of the disclosed embodiments described herein. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions.
[0027] The following are examples. In the following examples and comparative examples, all the raw materials used were obtained from commercial sources.
[0028] Preparation Example 1
[0029] Preparation of graphite emulsion:
[0030] 11 wt% of graphite was mixed with 1.5 wt% of ammonia water, and debonded with a sander equipped with steel balls for 1 hour. Then 1.5 wt% of polyvinyl pyrrolidone, 3 wt% of silica sol, 10 wt% of carboxymethyl cellulose, and 82 wt% of water were added and mixed, stirred for 1 hour, and then fixed with an electromagnet to remove iron after stirring evenly, and the sample was placed for 10 hours, and then shaken on a rocking machine for 1 hour to obtain graphite emulsion.
[0031] Preparation Example 2
[0032] Preparation of glass powder:
[0033] 50 wt% of SiO2, 30 wt% of PbO, 1 wt% of Al2O3, 10 wt% of Na2O, 0.5 wt% of K2O, 2.5 wt% of MgO, and 6 wt% of CaO are fully mixed to obtain glass powder.
[0034] Example 1
[0035] Step 1: Change the particle size D 50 Silver powder with a particle size of 1 μm was mixed with the graphite emulsion obtained in Preparation Example 1 at a weight ratio of 1:0.2, stirred for 1 hour, and dried at 80° C. for 4 hours to obtain a composite material.
[0036] Step 2: Mix 80 wt % of the composite material prepared in step 1, 3 wt % of glass powder (obtained in Preparation Example 2), 16.6 wt % of diethylene glycol butyl ether acetate, 0.2 wt % of castor oil leveling agent and 0.2 wt % of dispersant BYK-W980, and use ultrasonic dispersion and three-roll mill mixing to evenly disperse the slurry to obtain a silver paste.
[0037] Example 2
[0038] Step 1: Change the particle size D 50 Silver powder with a particle size of 1 μm was mixed with the graphite emulsion obtained in Preparation Example 1 at a weight ratio of 1:0.5, stirred for 1 hour, and dried at 80° C. for 4 hours to obtain a composite material.
[0039] Step 2: Mix 80 wt % of the composite material prepared in step 1, 3 wt % of glass powder (obtained in Preparation Example 2), 16.6 wt % of diethylene glycol butyl ether acetate, 0.2 wt % of castor oil leveling agent and 0.2 wt % of dispersant BYK-W980, and use ultrasonic dispersion and three-roll mill mixing to evenly disperse the slurry to obtain a silver paste.
[0040] Example 3
[0041] Step 1: Change the particle size D 50 Silver powder with a diameter of 3 μm was mixed with the graphite emulsion obtained in Preparation Example 1 at a weight ratio of 1:0.2, stirred for 1 hour, and dried at 80° C. for 4 hours to obtain a composite material.
[0042] Step 2: Mix 80 wt % of the composite material prepared in step 1, 3 wt % of glass powder (obtained in Preparation Example 2), 16.6 wt % of diethylene glycol butyl ether acetate, 0.2 wt % of castor oil leveling agent and 0.2 wt % of dispersant BYK-W980, and use ultrasonic dispersion and three-roll mill mixing to evenly disperse the slurry to obtain a silver paste.
[0043] Example 4
[0044] Step 1: Change the particle size D 50 Silver powder with a particle size of 1 μm was mixed with the graphite emulsion obtained in Preparation Example 1 at a weight ratio of 1:0.2, stirred for 1 hour, and dried at 60° C. for 8 hours to obtain a composite material.
[0045] Step 2: Mix 85 wt % of the composite material prepared in step 1, 2 wt % of glass powder (obtained in Preparation Example 2), 12.6 wt % of diethylene glycol butyl ether acetate, 0.2 wt % of castor oil leveling agent and 0.2 wt % of dispersant BYK-W980, and use ultrasonic dispersion and three-roll mill mixing to evenly disperse the slurry to obtain a silver paste.
[0046] Example 5
[0047] Step 1: Change the particle size D 50 Silver powder with a particle size of 1 μm was mixed with the graphite emulsion obtained in Preparation Example 1 at a weight ratio of 1:0.8, stirred for 1 hour, and dried at 80° C. for 4 hours to obtain a composite material.
[0048] Step 2: Mix 80 wt % of the composite material prepared in step 1, 3 wt % of glass powder (obtained in Preparation Example 2), 16.6 wt % of diethylene glycol butyl ether acetate, 0.2 wt % of castor oil leveling agent and 0.2 wt % of dispersant BYK-W980, and use ultrasonic dispersion and three-roll mill mixing to evenly disperse the slurry to obtain a silver paste.
[0049] Example 6
[0050] The method of Example 1 is followed, except that the silver powder and graphite emulsion are only mixed but not dried, that is:
[0051] Step 1: Change the particle size D 50 Silver powder with a diameter of 1 μm was mixed with the graphite emulsion obtained in Preparation Example 1 at a weight ratio of 1:0.2 to obtain a composite material.
[0052] Step 2: Mix 80 wt % of the composite material prepared in step 1, 3 wt % of glass powder (obtained in Preparation Example 2), 16.6 wt % of diethylene glycol butyl ether acetate, 0.2 wt % of castor oil leveling agent and 0.2 wt % of dispersant BYK-W980, and use ultrasonic dispersion and three-roll mill mixing to evenly disperse the slurry to obtain a silver paste.
[0053] Comparative Example 1
[0054] 80 wt% of the particle size D 50 1 μm silver powder, 3 wt % glass powder (obtained in Preparation Example 2), 16.6 wt % diethylene glycol butyl ether acetate, 0.2 wt % castor oil leveling agent and 0.2 wt % dispersant BYK-W980 are mixed, and ultrasonic dispersion and three-roll mill mixing are used to evenly disperse the slurry to obtain a silver paste.
[0055] Test Case
[0056] Performance test: The resistivity, contact resistivity, peel strength and aging performance of the electrodes prepared with the conductive silver pastes of the embodiment and the comparative example were tested respectively. The results are shown in Table 1.
[0057] (1) Test method of resistivity: The conductive pastes of the embodiment and the comparative example were screen-printed and coated on the N-type TOPCon solar blue film, and vacuum dried at room temperature for 3 hours. Then, it was cured using circulating hot air at 200°C for 30 minutes to obtain a fine-wire electrode. The resistance of the fine-wire electrode was then measured using an AEMC 6240 microresistance meter, and the width and length of the fine wire were measured using a WI-5000 interferometric coaxial three-dimensional stereo microscope. The pattern specifications of the fine-wire electrode formed above are that the width of the middle line segment is 40μm, the length is 9cm, and the contact pads at the head and tail are 2mm×2mm. The line resistance is measured by four-terminal sensing between the contact pads, and the measured resistance is standardized by the grid line length and multiplied by the cross-sectional area (measured using an α step profiler) to obtain the resistivity of the grid line. Each resistivity data set is obtained by averaging the values measured on four different grid lines.
[0058] (2) Test method for contact resistivity: The conductive pastes of the embodiment and the comparative example were screen-printed and coated on an N-type TOPCon solar blue film, and vacuum dried at room temperature for 3 hours. Then, the film was cured using circulating hot air at 200°C for 50 minutes to obtain a fine-line electrode. The electrode pattern consisted of 5 linear electrodes with a line width of 0.5 mm and a length of 50 mm, with a line spacing of 3 mm. Then, an AEMC 6240 microresistance meter was used to measure the resistance between line electrodes with different spacings, and the distance was calculated using the transmission line model method (TLM) to obtain the contact resistivity (R c ).
[0059] (3) Test method for peel strength: The conductive pastes of the embodiment and the comparative example were screen-printed and coated on the N-type TOPCon solar blue film, and vacuum dried at room temperature for 3 hours. Then, it was cured using circulating hot air at 200°C for 50 minutes to obtain a fine-wire electrode. To obtain an electrode pattern. The pattern specifications of the test electrode are 5 cm long and 2 mm wide, and then a tinned copper strip with a width of 1 mm is welded to the test electrode. The substrate is fixed on the tensiometer platform to test the peel strength. The tensiometer type is NLB-□100 electronic push-pull pressure gauge. The test conditions are to peel off the solder strip at an angle of 180° at a speed of 60 mm / min, and obtain the tensile force value, which is recorded every 1 second. The tension obtained is the average value of a 5 cm long electrode.
[0060] (4) Test method for aging resistance: Test the attenuation of the photoelectric conversion efficiency after 200 hot and cold cycles. Aging resistance (attenuation %) = (initial photoelectric conversion efficiency - photoelectric conversion efficiency after 200 hot and cold cycles) / initial photoelectric conversion efficiency × 100%.
[0061] Table 1
[0062]
[0063] It can be seen from the above table that the silver paste for solar cells prepared by the formula of the present invention can significantly reduce the resistivity and contact resistivity. The resistivity can be increased from 9.3×10 -6 Ω·cm decreased to 5.9×10 -6 Ω·cm, the contact resistivity can be from 3.6Ω·cm 2 Reduce 0.70×10 -6 Ω·cm. At the same time, it can also improve the peel strength and aging resistance.
[0064] The present application is not limited to the embodiments described above, and various modifications and changes may be made without departing from the scope thereof. The scope of the present application is limited only by the appended claims.
[0065] In the present application, each embodiment may focus on the differences from other embodiments, and the same or similar parts between the embodiments may refer to each other.
Claims
1. A silver paste comprising a composite material, glass powder and an organic carrier, wherein: The raw materials of the composite material include silver powder and graphite emulsion.
2. The silver paste according to claim 1, characterized in that The preparation method of the composite material comprises: mixing silver powder and graphite emulsion and drying.
3. The silver paste according to claim 2, characterized in that In terms of weight percentage, the graphite emulsion contains 9-11 weight % of graphite, 1-2 weight % of dispersant, 2-4 weight % of binder, 1-2 weight % of ammonia water, 0.8-1.8 weight % of thickener, and 81-85 weight % of water; Preferably, the dispersant is selected from one or more of sodium carboxymethyl cellulose, polyvinyl pyrrolidone, polyvinyl alcohol and gum arabic; Preferably, the binder is selected from silica sol; Preferably, the thickener is selected from carboxymethyl cellulose.
4. The silver paste according to claim 2 or 3, characterized in that The weight ratio of silver powder to graphite emulsion is 1:0.2-0.5; and / or, The particle size of the silver powder is 0.5-5 μm; and / or, The drying conditions include: a temperature of 60-100° C. and a time of 2-10 hours.
5. The silver paste according to any one of claims 1 to 4, characterized in that Based on the total weight of the silver paste, the content of the composite material is 50-85 weight %, the content of the glass powder is 2-5 weight %, and the content of the organic vehicle is 14-45 weight %.
6. The silver paste according to any one of claims 1 to 5, characterized in that The glass powder is selected from one or more of borosilicate glass powder, alkali metal glass powder, ultra-white rolled glass powder and ultra-white float glass powder.
7. The silver paste according to any one of claims 1 to 6, characterized in that The organic vehicle comprises a solvent and optional additives; Preferably, the solvent is selected from one or more of diethylene glycol butyl ether acetate, dimethyl glutarate, dimethyl succinate and dimethyl adipate; Preferably, the additive is selected from one or more of a dispersant, a leveling agent, a thixotropic agent, a coupling agent and a defoaming agent.
8. The silver paste according to any one of claims 1 to 7, characterized in that The silver paste is a conductive silver paste for the front side of a solar cell.
9. The method for preparing the silver paste according to any one of claims 1 to 8, comprising: Silver powder, composite material and organic vehicle are mixed.
10. Use of the silver paste according to any one of claims 1 to 8 in solar cells.
Citation Information
Patent Citations
Preparation method of graphene compound silver paste and graphene compound silver paste
CN103811130A
High-solderability front-surface electrode silver paste of crystalline silicon solar cell and preparation method of high-solderability front-surface electrode silver paste
CN107887050A
High-solderability composite silver electrode slurry for crystalline silicon solar cells and preparation method for high-solderabilitycomposite silver electrode slurry
CN108777184A
Conductive paste, preparation method and electronic device comprising conductive paste
CN115458205A
Silver-Coated Graphite Particles, Silver-Coated Graphite Mixed Powder and Production Method Therefor, and Conductive Paste
US20180362348A1